THE IMPACT OF HEAVY METALS (CADMIUM & NICKEL) ON SEED GERMINATION, PHOTOTHYNSISES PIGMENTS AND VEGETATIVE GROWTH OF FENUGREEK (Trigonell afoenum-Graecum) PLANT - FAIZY, HADAR SAID; SAHI, BALQES G.; MAHDI , HONAR SAFAR; HAMID, HARIKAR MOHAMMED SALIH (Journal of Duhok University, 2022)
This study was conducted at the College of Agricultural Engineering Science, University of Duhok, Kurdistan region. The aim of this work is to study the influence of Cadmium at (0, 50, 100) mg/kg-1 and Nickel fertilizer at (0, 50, 100, 150) mg/kg-1 concentrations on the seed germination, photosynthesis pigments and vegetative part of Trigonell afoenum-graecum .The results conducted that the heavy metals (Cd and Ni) and interaction between 50mg/kg-1 of nickel with control has a significant effect on the high of plant. Moreover, the 100 mg/kg-1 of cadmium and the interaction of 100 mg/kg-1 cadmium with control of nickel produce a high value of fresh weight of vegetative part, in addition, the application of 100 mg/kg-1 cadmium and combination with the control and interaction between 100 mg/kg-1 of cadmium and nickel had a great effect on the weight of root. The dry weight of plant was improved by adding 100 mg/kg-1   for each of cadmium and nickel but the best value was the combination of 100 mg/kg-1 of cadmium with nickel, as well as, the interaction 50 mg/kg-1 of cadmium with control had great impact on the seed germination, There was a significant influence of Cd and Ni on the 50 mg/kg-1 and 100 mg/kg-1 of cadmium and 150 mg/kg-1 of nickel, ß carotene 100 mg/kg-1  both of the Cd and Ni, while the total carotene concentration was effected by the 50 mg/kg-1 for both and 150 mg/kg-1 of nickel and Zeazanthen concentration 100mg/kg-1 of cadmium with effect of all levels of nickel, additionally, the concentration of £ carotene, ß carotene and Zeazanthen was effected by the interaction of 100 mg/kg-1 of Cd and Ni and interaction of all levels of Cd and Ni was significantly affected total carotene concentration